Short Communication: Carbon sequestration by young Rhizophora apiculata plants in Kubu Raya District, West Kalimantan, Indonesia - RINTO WIARTA; YULIATI INDRAYANI; FAIRUZ MULIA; DWI ASTIANI (Biodiversitas Journal of Biological Diversity, 2019)
Wiarta R, Indrayani Y, Mulia F, Astiani D. 2019. Short Communication: Carbon sequestration by young Rhizophora apiculata plants in Kubu Raya District, West Kalimantan, Indonesia. Biodiversitas 20: 311-315. Mangrove forest ecosystem has been known for its roles in buffering coastal abrasions and being a reservoir for seafood production. However, very little information is available on its role in sequestering carbon and how its annual growth ability can benefit climate change mitigation. This study aims to determine carbon storage and sequestration by one, three and five-year-old Rhizophora apiculata Blume planted in PT. Ovivipari Bina Semesta (PT. BIOS). This study was conducted for over five months during 2015-2016, in purposively selected mangrove rehabilitation area. It used both harvestings as well as non-harvesting methods for estimation of carbon stock and carbon sequestration. The results show that the mangrove species has a very high ability to sequester carbon per unit area. The amount of carbon stored in plants aged 1 year, 3 years and 5 years were 0.363 tonnes ha-1, 5,591 tonnes ha-1 and 7,240 tons ha-1, respectively. The study also indicated that the carbon stock values obtained by non-harvesting method using allometric equation were higher than the values obtained by harvesting method.